Agarose Gel Electrophoresis. Issue 10 (1st May 2015) - Armstrong, Jennifer A.; Schulz, Joseph R.
Abstract: Agarose gel electrophoresis, which separates and sizes linear DNA and RNA fragments, is arguably the most basic and essential technique in molecular biology. It is commonly employed for analysis of PCR products, plasmid DNA, and products of restriction enzyme digestion. It is the first step for analysis of specific DNA and RNA fragments by northern and Southern blots. In this unit, we provide both written instructions and photographic images to take the reader from preparing a first agarose gel to analyzing results and determining the size of sample DNA. We include two protocols: agarose gel electrophoresis (commonly used to analyze DNA) and denaturing gel electrophoresis (for analyzing RNA). We have divided each protocol into four basic steps: (1) preparing and pouring the agarose gel; (2) preparing and loading samples; (3) running the agarose gel; and (4) staining the gel using the fluorescent stain ethidium bromide to visualize DNA and RNA. © 2015 by John Wiley & Sons, Inc.